(untitled) (Ameghiniana, 2013)
In the present paper descriptions are given of 19 specíes of microspores included in 12 different genera. One of the latter and 15 of the former are proposed as new to science. They correspond only to trilete, monocolpate and bisaccate grains and they belong to the upper section of the Los Rastros Formation, Ischigualasto area, San Juan Province (Argentina). This formation is usually considered of Upper Triassic age (Norían ), Special attention is devoted to some monocolpate genera (Cycadopites, Entylissa, Lagenella, etc.) and emmendatíons which are thought to make thern useful are proposed. In view of the shortness of the profile and the relative scantiness of most of the species, no attempts are made to establish zonations or correlations with other areas.